2016
DOI: 10.7567/jjap.55.045503
|View full text |Cite
|
Sign up to set email alerts
|

Growth process of hydrogenated amorphous carbon films synthesized by atmospheric pressure plasma enhanced CVD using nitrogen and helium as a dilution gas

Abstract: Hydrogenated amorphous carbon films with various thicknesses were synthesized by dielectric barrier discharge-based plasma deposition under atmospheric pressure diluted with nitrogen (N2) and helium (He) at various pulse frequencies. The C2H2/N2 film showed cauliflower-like-particles that grew bigger with the increase in film’s thickness. At 5 kHz, the film with a thickness of 2.7 µm and smooth surface was synthesized. On the other hand, the films synthesized from C2H2/He had a smooth surface and was densely p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…In argon gas the dominant influence in plasma sputtering is a physical reaction. Argon atoms are heavy atoms with low reactive properties, so it would be more effective if used to target materials for deposition of thin films [8,11].…”
Section: акумуляторнI вIдходи -це вIдходи якI можуть завдати шкоди нmentioning
confidence: 99%
See 3 more Smart Citations
“…In argon gas the dominant influence in plasma sputtering is a physical reaction. Argon atoms are heavy atoms with low reactive properties, so it would be more effective if used to target materials for deposition of thin films [8,11].…”
Section: акумуляторнI вIдходи -це вIдходи якI можуть завдати шкоди нmentioning
confidence: 99%
“…Amorphous carbon layer has been widely used in industry and research. The amorphous carbon layer has a wide variety of properties of mechanical, physical, biomedical, and tribological so that it can be utilized in broad applications as well [6][7][8]. Carbon atoms that have sp 3 hybridization have stronger bonds, so as to increase the hardness value of the thin layer of carbon material [7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared to other studies involving AC voltage with high frequency DBD ethylene plasma (Fanelli et al 2005), the deposition rates for our alkane plasmas are ten times smaller. Using acetylene as gas feed precursor, Mori et al (2016) observed that the hydrogenated amorphous carbon poly- Figure 3. FTIR spectra of the He/C n H 2n+2 gas mixtures, sampled before and after 6 hours of DBD plasma processing.…”
Section: Hydrogenated Amorphous Carbon Filmsmentioning
confidence: 99%